The effect of in ovo injection of hatching eggs with omega-3 oil on some productive traits of broilers - Majida Mourad Zghair Kattan; Muhammad Jodi Shahid (University of Thi-Qar Journal of agricultural research, 2021)
This study was conducted to investigate the effect of in ovo injection of hatching eggs with Omega 3 Oil at 18 days old, in the amniotic sac in the air sac, on some productive characteristics of broilers ROSS 308. The eggs were injected into the Al-Bazz hatchery in the holy governorate of Karbala, as for raising hatched chicks from injected eggs, it was conducted in the poultry hall in the research station of the Department of Animal Production, College of Agriculture and Marshes, Thi-Qar University, from 12/1/2020 to 25/1/2021. A total of 450 eggs from ROSS 308 broiler breeder were used in this experiment, distributed into five treatments as follows: T1; The first treatment (negative control): hatching eggs left without injection. T2; The second treatment (positive control): hatching eggs injected with sunflower oil. And another treatment T3, T4 and T5 were injected hatching eggs with 0.1, 0.2 and ml of omega-3 oil respectively. 300 chicks from the hatched chicks were distributed in cages with dimensions of 1 x 1.5 m for each cage, at a rate of 60 chicks for each treatment, with three replicates of the treatment (20 chicks for each replicate). The results of the study indicated that there was a significant (P < 0.05) improvement in the studied productive traits (body weight, weight gain, feed intake, feed conversion factor).